Does maternal hydronephrosis have an impact on urinary neutrophil gelatinase-associated lipocalin (uNGAL) levels?. (19th March 2017) - Pabuccu, Emre G.; Caglar, Gamze Sinem; Kiseli, Mine; Yarci Gursoy, Asli; Candar, Tuba; Tangal, Semih; Ergun, İhsan
Abstract: Objective : To determine urinary neutrophil gelatinase-associated lipocalin (uNGAL) levels and creatinine clearance values in women with different degrees of asymptomatic hydronephrosis during pregnancy. Methods : A total of 44 pregnant women with different degrees of hydronephrosis and 46 without hydronephrosis were consecutively enrolled in this prospective study. Basic serum and urine parameters, uNGAL levels, and creatinine clearance values were evaluated. All results were compared between the two groups. Regression analysis was used to determine independent predictors, which were mostly related to hydronephrosis. Results : Demographic data, basal laboratory parameters, and creatinine clearance values were similar, whereas significantly higher uNGAL levels were detected in women with hydronephrosis compared to those without hydronephrosis (45.3 versus 33.2 ng/mL, respectively) ( p = 0.004). An increasing trend in uNGAL levels was detected with increasing degrees of hydronephrosis; as it was not statistically significant ( p = 0.163). Linear regression analysis revealed that the parameter of "pelvic diameter" was found as a significant independent factor influencing uNGAL concentrations ( β = 0.289; 95% CI: 0.522–3.061; p = 0.006). Other independent variables were not found to influence uNGAL concentrations ( p > 0.05). Conclusion : The results obtained from this study indicate a significant increase of urinary concentration of NGAL in the presence of asymptomatic maternal hydronephrosis. This impact is likely to be more profound in those with severe hydronephrosis although this has not been specifically investigated. This theory needs to be validated in larger populations.